Effectiveness of a Shoulder Exercise Program in Division I Collegiate Baseball Players During the Fall Season - Hillary A. Plummer; Shannon M. Plosser; Paul R. Diaz; Nicholas J. Lobb; Lori A. Michener (North American Sports Medicine Institute, 2022)
# Background Deficits in shoulder range of motion (ROM) and strength are associated with risk of arm injury in baseball players. # Purpose The purpose of this study was to assess the effectiveness of a standardized exercise program, during the fall season, on shoulder ROM and rotational strength in collegiate baseball players. # Study Design Prospective cohort study # Methods Passive shoulder internal rotation (IR), external rotation (ER), and horizontal adduction ROM were measured with an inclinometer. Shoulder IR and ER strength was assessed using a hand-held dynamometer and normalized to body weight. Players performed a program of shoulder stretching and strengthening exercises, three times/week for one month and then one time/week for two months. Paired sample t-tests compared pre-intervention to post-intervention outcome measures. # Results Division I baseball players (n=43; 19.6±1.2years, 185.8±5.5cm, 90.5±7.0kg) volunteered. From pre- to post-intervention, there were increases in horizontal adduction ROM in the throwing (Mean Difference (MD)=6.1°, 95%CI=3.7,8.5; p\<0.001) and non-throwing arm (MD=8.0°, 95%CI=5.6,10.3; p\<0.001), and a decrease in non-throwing arm ER ROM (MD=2.8°, 95%CI= 0.2,5.5; p=0.039). The ER ROM surplus (throwing -- non-throwing) increased (MD=5.6°, 95%CI= 1.1,10.2; p=0.016). Throwing arm (MD=1.3%BW, 95%CI=0.5-2.1, p=0.003) and non-throwing arm (MD=1.2%BW, 95%CI=0.4,2.0; p=0.004) ER strength decreased. A notable, but non-significant increase in IR strength on the throwing arm (MD=1.6%BW, 95%CI=0.1,3.0; p=0.055) and decrease on the non-throwing arm (MD=1.2%BW, 95%CI=0.0,2.4; p=0.055) occurred. Additionally, throwing arm ER:IR strength ratio (MD=0.16, 95%CI=0.08,0.25; p\<0.001) also decreased. # Conclusion Changes in shoulder horizontal adduction ROM, IR strength and relative ER surplus on the throwing arm were noted at the end of the season. The lack of change in IR and ER ROM and may be related to the lack of deficits at the start of the fall season. # Level of Evidence 2\.